Exosomal Circular RNA as a Biomarker Platform for the Early Diagnosis of Immune-Mediated Demyelinating Disease - He, Jinting; Ren, Ming; Li, Haiqi; Yang, Le; Wang, Xiaofeng; Yang, Qiwei (Frontiers in Genetics, 2019)
Exosomes can pass through the blood-brain barrier and are present in the cerebrospinal fluid (CSF). The components in exosomes, such as DNA, RNA, protein and lipids, change greatly and are closely related to disease progression. Circular RNA (circRNA) is stable in structure and has a long half-life in exosomes without degradation. Therefore, circRNA is considered an ideal biomarker and can be used to monitor a variety of central nervous system diseases. This study aimed to investigate the expression profiles of exosomal circRNA (exo-circRNA) in CSF from patients with immune-mediated demyelinating diseases to identify suitable biomarkers for the early diagnosis of immune-mediated demyelinating diseases. circRNA expression levels in exosomes obtained from five CSF samples from immune-mediated demyelinating disease patients and five paired CSF control samples were analyzed using a hybridization array. Hierarchical clustering analysis showed that 5095 exo-circRNAs were differentially expressed between patients with immune-mediated demyelinating diseases and paired control samples. Of these exo-circRNAs, 26 were identified as significantly differentially expressed in CSF exosomes from patients with immune-mediated demyelinating diseases (FC ≥1.5 and p-values ≤0.05). GO and KEGG enrichment analysis indicated that the upregulation or activation of PTPRF and RAD23B may be associated with the occurrence and development of immune-mediated demyelinating diseases. Then, a competing endogenous RNA network was constructed and centered on the most up/downregulated exo-circRNAs to predict their function in immune-mediated demyelinating diseases. Additionally, reverse transcription quantitative polymerase chain reaction results stating that hsa_circ_0087862 and hsa_circ_0012077 were validated in an independent cohort of subjects. Canonical correlation analysis results indicated a potential connection between exosomal hsa_circ_0012077 expression level and IgG levels in CSF. Finally, the ROC curve showed that when hsa_circ_0087862 or hsa_circ_0012077 was employed alone for diagnosing immune-mediated demyelinating diseases, the diagnostic accuracy was 100%. In conclusion, based on this study, exosomal hsa_circ_0087862 and hsa_circ_0012077 in CSF could be used as suitable biomarkers for a diagnosis of immune-mediated demyelinating disease based on their expression levels. Moreover, the upregulation or activation of PTPRF and RAD23B was potentially associated with the occurrence and development of immune-mediated demyelinating diseases.